2020
DOI: 10.1002/jbio.202000040
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral imaging and characterization of allergic contact dermatitis in the short‐wave infrared

Abstract: Short‐wave infrared hyperspectral imaging is applied to diagnose and monitor a case of allergic contact dermatitis (ACD) due to poison ivy exposure in one subject. This approach directly demonstrates increased tissue fluid content in ACD lesional skin with a spectral signature that matches the spectral signature of intradermally injected normal saline. The best contrast between the affected and unaffected skin is achieved through a selection of specific wavelengths at 1070, 1340 and 1605 nm and combining them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…FLIM collected datasets were analyzed using IDCube software (HSpeQ LLC, USA) that process 3D spectral data ( 22 ). FLIM raw data were first converted to the IDCube format and processed using a three- band method to generate a pseudo RGB image ( 23 ). The generated image is a composite of the three selected bands (time channels, i.e.)…”
Section: Methodsmentioning
confidence: 99%
“…FLIM collected datasets were analyzed using IDCube software (HSpeQ LLC, USA) that process 3D spectral data ( 22 ). FLIM raw data were first converted to the IDCube format and processed using a three- band method to generate a pseudo RGB image ( 23 ). The generated image is a composite of the three selected bands (time channels, i.e.)…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we believe that the HSI analysis technique may play a role in the investigation of asymptomatic skin change in T2DM patients with sudomotor dysfunction and play a role in clinical application for the early detection of DN. According to the existing literature, the SWIR region (defined as wavelength: 1000-2000 nm) is useful for obtaining additional quantitative information about the composition of biological tissues, which include components such as water, lipid and collagen [50][51][52][53]. Previous studies have found that collagen exhibits a low absorption coefficient near the wavelength of 1050 nm; water exhibits an absorption peak near the wavelength of 1450 nm [50,51,54].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the optical properties of biological tissues, HSI is limited to surfaces, near-surface structures, or samples/tissues of penetrable thicknesses. 1,5,21,38,48,81,[87][88][89][90][91][92][93][94][95] Thus, HSI is not a direct competitor of other medical imaging modalities such as ultrasound, magnetic resonance imaging, or X-rays; it is a complementary or additional technique.…”
Section: Medical Hyperspectral Imagingmentioning
confidence: 99%
“…Initial studies include examples on circulatory changes and skin oxygenation in diabetic feet. 93 Allergic contact dermatitis, burns, and ulcers are more recent examples of HSI of skin 75,93,94 (Fig. 5.5).…”
Section: Medical Hyperspectral Imagingmentioning
confidence: 99%